Krüppel-Like Factor 6 Silencing Prevents Oxidative Stress and Neurological Dysfunction Following Intracerebral Hemorrhage via Sirtuin 5/Nrf2/HO-1 Axis - Sun, Jia; Cai, Jinzhong; Chen, Junhui; Li, Siqiaozhi; Liao, Xin; He, Yixuan; Chen, Xudong; Hu, Sean (Frontiers in Aging Neuroscience, 2021)
As a severe neurological deficit, intracerebral hemorrhage (ICH) is associated with overwhelming mortality. Subsequent oxidative stress and neurological dysfunction are likely to cause secondary brain injury. Therefore, this study sought to define the role of Krüppel-like factor 6 (KLF6) and underlying mechanism in oxidative stress and neurological dysfunction following ICH. An in vivo model of ICH was established in rats by injection of autologous blood, and an in vitro ICH cell model was developed in hippocampal neurons by oxyhemoglobin (OxyHb) exposure. Next, gain- and loss-of-function assays were performed in vivo and in vitro to clarify the effect of KLF6 on neurological dysfunction and oxidative stress in ICH rats and neuronal apoptosis and mitochondrial reactive oxygen species in OxyHb-induced hippocampal neurons. KLF6, nuclear factor erythroid 2–related factor 2 (Nrf2), and heme oxygenase 1 (HO-1) were highly expressed in hippocampal tissues of ICH rats, whereas sirtuin 5 (SIRT5) presented a poor expression. Mechanistically, KLF6 bound to the SIRT5 promoter and transcriptionally repressed SIRT5 to activate the Nrf2/HO-1 signaling pathway. KLF6 silencing alleviated neurological dysfunction and oxidative stress in ICH rats and diminished oxidative stress and neuronal apoptosis in OxyHb-induced neurons, whereas SIRT5 overexpression negated its effect. To sum up, KLF6 silencing elevated SIRT5 expression to inactivate the Nrf2/HO-1 signaling pathway, thus attenuating oxidative stress and neurological dysfunction after ICH.